The Evolution of Digital Transformation in Chinese Manufacturing: A Review Amidst the Drive for High-Quality Development - Huihong, Chen; Bhaumik, Amiya (International Journal of Advances in Business and Management Research (IJABMR), 2025)
Chinese businesses now have more chances than ever before to achieve high-quality development because of the rise of the digital economy. There are several issues that have arisen as a result of digital transformation in Chinese manufacturing enterprises. These include a severe lack of digital transformation talent, an incomplete pattern of collaborative innovation throughout the industrial chain, and a lack of a solid foundation for digital transformation in Chinese enterprises. Using findings from field investigations and literature reviews, this paper lays out a theoretical framework and process for digital transitions in enterprises. It then proposes a top-tier design that includes data resource accumulation, digital platform, and the construction of a benign collaborative ecological system. All of this will take place against the backdrop of developing high-quality digital transformation and the trajectory for the growth. The significance of digital transformation and its role in helping companies maintain market competitiveness of economies. However, environmental, social, and institutional factors are also affected by disruptive changes that happen at the corporate level. Because of this, a broad variety of issues related to digital transformation have been extensively studied in academic literature during the 20 years.